IDENTIFIKASI POTENSI PEMANFAATAN EKOWISATA DAN JASA LINGKUNGAN KABUPATEN SAMOSIR - Simarmata, Marulam MT; Triastuti (PRODI KEHUTANAN UNIVERSITAS SIMALUNGUN, 2021)
Abstract: The research aims to identify the utilization of Ecotourism and environmental services in Samosir Regency.The research was conducted using the tracking path to find potential locations that have the potential to have environmental services and tourist objects, which are then processed and with the support of available data, which is then carried out by a SWOT analysis as an effort to utilize and identify potential environmental services and natural tourism as well as making strategies for the utilization of environmental services and natural tourism.Based on the results of the analysis, the identification of the use of Ecotourism and environmental services in Samosir Regency is very supportive of tourism development in Samosir Regency. The results of the mapping of the tourist attraction tracking path found 3 potential locations in Harian District and 4 potential locations in Simanindo District with landscape activities, camping ground, out bound and relaxing hills. Â Â